2017
DOI: 10.1007/s00167-017-4814-1
|View full text |Cite
|
Sign up to set email alerts
|

No risk of arthrofibrosis after acute anterior cruciate ligament reconstruction

Abstract: PurposeTo compare acute ACL reconstruction (ACLR) within 8 days of injury with delayed reconstruction after normalized range of motion (ROM), 6–10 weeks after injury. It was hypothesized that acute ACL reconstruction with modern techniques is safe and can be beneficial in terms of patient-reported outcomes and range of motion.MethodsSample size calculation indicated 64 patients would be required to find a 5° difference in ROM at 3 months. Seventy patients with high recreational activity level, Tegner level 6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 30 publications
5
89
0
Order By: Relevance
“…This study supports the findings of other recent studies which have demonstrated that the timing of ACLR does not influence postoperative ROM [ 1 , 7 , 10 , 17 , 24 ] and contradicts the findings of older studies including Shelbourne et al [ 25 , 28 , 37 ]. These differences may be due to the fact that these older studies were performed without the use of contemporary arthroscopic techniques, were retrospective, and perhaps most importantly had a more restrictive postoperative rehabilitation regime.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study supports the findings of other recent studies which have demonstrated that the timing of ACLR does not influence postoperative ROM [ 1 , 7 , 10 , 17 , 24 ] and contradicts the findings of older studies including Shelbourne et al [ 25 , 28 , 37 ]. These differences may be due to the fact that these older studies were performed without the use of contemporary arthroscopic techniques, were retrospective, and perhaps most importantly had a more restrictive postoperative rehabilitation regime.…”
Section: Discussionsupporting
confidence: 86%
“…The current recommendation is to delay ACLR after an acute injury due to the risk of arthrofibrosis and suboptimal clinical results [ 28 , 37 ]. However, several studies have shown similar postoperative range of motion (ROM) regardless of whether surgery was performed within 48 h, 2 weeks, or if ACLR was delayed for a minimum of 6 weeks [ 1 , 10 , 17 , 22 , 30 ]. Early ACLR can facilitate early return to sport and work, and has been reported to be more cost effective, while increased time between injury and surgical intervention is associated with increased incidence of meniscus and cartilage injuries [ 9 , 20 , 23 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no accepted definition for early or delayed ACLR (Beynnon et al, 2005), with "early" defined as between two days and seven months of DOI, and "delayed" as between three weeks and 24 years (Anderson et al, 2016). There are equivocal differences in outcomes between patients undergoing early verses delayed ACLR (Anderson et al, 2016;Eriksson, von Essen, Jönhagen, & Barenius, 2018;Lee, Lee, Lee, & Hui, 2018;Smith, Postle, Penny, McNamara, & Mann, 2014;Wittenberg, Oxfort, & Plafki, 1998), although early surgical intervention may reduce the risk of subsequent meniscal or chondral injury, both of which are associated with worse outcomes following ACLR (Cinque et al, 2018;Cox et al, 2014).…”
Section: Time To Surgerymentioning
confidence: 99%
“…There is no accepted definition for early or delayed ACLR (Beynnon et al, 2005), with "early" defined as between two days and seven months of DOI, and "delayed" as between three weeks and 24 years (Anderson et al, 2016). There are equivocal differences in outcomes between patients undergoing early verses delayed ACLR (Anderson et al, 2016;Eriksson, von Essen, Jönhagen, & Barenius, 2018;Lee, Lee, Lee, & Hui, 2018;Smith, Postle, Penny, McNamara, & Mann, 2014;Wittenberg, Oxfort, & Plafki, 1998), although early surgical intervention may reduce the risk of subsequent meniscal or chondral injury, both of which are associated with worse outcomes following ACLR (Cinque et al, 2018;Cox et al, 2014).…”
Section: Time To Surgerymentioning
confidence: 99%